Study and Analyze the Value of Kathin Merit-Making That Influences Thai Society - Sirintam, Parita; Somchit, Somchai; Khammuangsaen, Boonruam (Journal of Dhamma for Life, 2025)
This research has three main objectives: 1) to study the concepts and theories of value in terms of Buddhism, philosophy, and social dimensions; 2) to explore the value in the "Thod Kathin" ceremony, reflecting religious, cultural, and economic aspects in Thai society; and 3) to analyze the influence of the "Thod Kathin" ceremony on Thai society, including its impacts on the mind, social relations, and the development of the economy and culture. The study uses qualitative research methods, focusing on analyzing documents from Buddhist scriptures, related research, and conducting in-depth interviews with monks, community leaders, and participants in the ceremony. The findings reveal that the "Thod Kathin" ceremony holds multi-dimensional value: Religious dimension: It nurtures Buddhism, enhances faith, and fosters unity among the community. Social and cultural dimension It acts as a center for social activities, promoting cooperation and generosity between individuals. Economic dimension It stimulates the local economy through spending on the ceremony and consumption of related goods and services. Psychological and ethical dimension It provides an opportunity for self-discipline through giving, sacrifice, and merit-making. The analysis concludes that the "Thod Kathin" ceremony is not only a religious ritual but also a vital mechanism that influences the stability of Buddhism, social harmony, and community-level economic development, reflecting profound values that affect Thai society in various ways.